Power loss estimation and simulation of a BLDC motor drive system - K.S., Rama Rao; Mayarisma, Denci (2008)
This paper presents the analysis and estimation of power losses in a Brushless DC (BLDC) motor drive system. Simulation is performed on the Pulse Width Modulated (PWM) inverter and BLDC motor drive system using the MATLAB/Simulink Toolbox and the performance characteristics are compared with experimental results. The optimal parameters of the inverter-motor drive system minimizing the losses are determined by an intelligent optimization method, the Simulated Annealing (SA) technique.